Should transportation output be included as part of the coincident indicators system? - Kajal Lahiri; Wenxiong Yao (Center for Economic Studies and ifo Institute (CESifo), 2011)
With the increasing importance of the service-providing sectors, information from these sectors has become essential to the understanding of contemporary business cycles. This paper explores the usefulness of the transportation services output index (TSI) as an additional coincident indicator in determining the peaks and troughs of U.S. economy. The index represents a service sector that plays a central role in facilitating economic activities between sectors and across regions, and can be useful in monitoring the current state of the economy. We evaluate the marginal contribution of the TSI in identifying cyclical turning points in the context of four currently used NBER indicators. The TSI is found to have advantages over the composite index of coincident indicators in identifying turning points, and has been of critical importance in recent recessions.
Keywords: E32; C10; 330; transportation services index (TSI); business cycles; coincident indicators; Spedition; Logistikunternehmen; Konjunkturindikator; Konjunkturprognose; Prognoseverfahren; USA